Pengaruh Risiko Pasar terhadap Profitabilitas Perusahaan Subsektor Bank pada Bursa Efek Indonesia - Nawir Mansyur (Jurnal Maksipreneur, 2018)
This study aims to analyze the effect of interest rate risk and exchange rate risk on the profitability of the company sub-sector of the bank in Indonesia Stock Exchange (IDX). This study uses panel data from 24 bank financial statements from 2011-2014. The analysis technique uses path analysis with Smart PLS 3.0. Exogenous variables of interest rate risk and foreign exchange rate risk and endogenous variables are profitability. The results of the study found that interest rate risk positively and significantly affects the profitability and exchange rate risk negatively and significantly affects the profitability of the company sub-sector of the bank in Indonesia Stock Exchange.